Nutritional status and food intake are related to malnutrition risk and length of stay in hospitalized patients - Yalçın, Tuba; Yürük, Armağan Aytuğ; Türkoğlu, İnci; Ilgaz, Fatma; Açıkgöz, Aylin; Aksan, Ayşegül; Gökmen Özel, Hülya; Akal Yıldız, Emine; Samur, Gülhan (Progress in Nutrition, 2018)
Objective: The aim was to evaluate the relationship between food intake and malnutrition risk of hospitalized patients. Methods: In this study 192 hospitalized patients were included.  Food intake was performed on 24 h recall dietary method Nutritional Risk Screening-2002 has been used to evaluate the nutritional status of patients. Odds ratios with 95% confidence intervals were computed using a univariate and multivariate stepwise logistic regression model with malnutrition risk as the response variable. Results: The mean age of individuals was 50.3±16.35 years, 29.4% of males and 20.0% of females were at risk group. The patients with malign neoplasms had the highest malnutrition risk score. The overall coverage of the energy, protein, fibre, vitamin C, vitamin B12, calcium, iron and the other micronutrients of the malnutrition risk group were significantly lower than well-nourished patients (p